2015
DOI: 10.1007/s00392-015-0919-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of novel oral anticoagulants in patients with bioprosthetic valves

Abstract: The use of NOAC therapy for AF in patients with bioprosthetic valves appears safe and effective in the occurrence of thromboembolic events, however, at the expense of increased bleeding. Larger studies are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…5 According to the practice guidelines of the European Heart Rhythm Association, patients with bioprosthetic heart valve or surgical valve repair are eligible to receive NOACs, expectedly for the first 3 to 6 months postoperatively. 6 Few clinical practice data are available in literature about the efficacy and safety of NOACs in AF patients with bioprosthetic heart valves or surgical valve repair, 11,12 and these patients were relatively underrepresented in trials performed to date. The RELY (Randomized Evaluation of Long-term Anticoagulant Therapy) trial excluded AF patients with prosthetic heart valve (biological or mechanical) and valvular disease requiring an intervention before study.…”
Section: Discussionmentioning
confidence: 99%
“…5 According to the practice guidelines of the European Heart Rhythm Association, patients with bioprosthetic heart valve or surgical valve repair are eligible to receive NOACs, expectedly for the first 3 to 6 months postoperatively. 6 Few clinical practice data are available in literature about the efficacy and safety of NOACs in AF patients with bioprosthetic heart valves or surgical valve repair, 11,12 and these patients were relatively underrepresented in trials performed to date. The RELY (Randomized Evaluation of Long-term Anticoagulant Therapy) trial excluded AF patients with prosthetic heart valve (biological or mechanical) and valvular disease requiring an intervention before study.…”
Section: Discussionmentioning
confidence: 99%
“…A sixty-seven-year-old male was initially admitted to our hospital with shortness of breath and severe aortic valve regurgitation ( Figure 1A atrial fibrillation with or without bioprosthetic valve due to the convenience and the potential reduction in the length of hospital stay. 1,6 However, GALILEO (Global Study Comparing a Rivaroxaban-based Antithrombotic Strategy to an Antiplatelet-based Strategy after TAVR to Optimize Clinical Outcomes) trial showed that rivaroxaban was associated with a higher risk of death or thromboembolic complications and a higher risk of bleeding than an antiplatelet-based strategy after successful transcatheter aortic valve replacement. 7 In addition, rebound thrombosis upon discontinuation of rivaroxaban was reported.…”
Section: A S Ementioning
confidence: 99%
“…31 One small pilot study compared dabigatran versus warfarin after bioprosthesis valve replacement for the management of AF postoperatively (DAWA pilot study), but small numbers preclude definitive conclusions. 32 Recent small studies also suggest that NOACs can be a reasonable alternative to VKA in patients with AF and remote bioprosthetic valve implantation; 22,33 however, larger studies are needed to define the safety and efficacy profile. Data on thromboprophylaxis in patients with AF and TAVI, which is actually the insertion of a bioprosthesis, are preliminary 34 and discussed in section 'Antithrombotic Therapy in Patients with AF Undergoing TAVI or Left Atrial Appendage Occlusion'.…”
Section: Bioprosthesesmentioning
confidence: 99%